The brain-body disconnect: A somatic sensory basis for trauma-related disorders - Kearney, Breanne E.; Lanius, Ruth A. (Frontiers in Neuroscience, 2022)
Although the manifestation of trauma in the body is a phenomenon well-endorsed by clinicians and traumatized individuals, the neurobiological underpinnings of this manifestation remain unclear. The notion of somatic sensory processing, which encompasses vestibular and somatosensory processing and relates to the sensory systems concerned with how the physical body exists in and relates to physical space, is introduced as a major contributor to overall regulatory, social-emotional, and self-referential functioning. From a phylogenetically and ontogenetically informed perspective, trauma-related symptomology is conceptualized to be grounded in brainstem-level somatic sensory processing dysfunction and its cascading influences on physiological arousal modulation, affect regulation, and higher-order capacities. Lastly, we introduce a novel hierarchical model bridging somatic sensory processes with limbic and neocortical mechanisms regulating an individual’s emotional experience and sense of a relational, agentive self. This model provides a working framework for the neurobiologically informed assessment and treatment of trauma-related conditions from a somatic sensory processing perspective.